IMPLEMENTASI PERATURAN DAERAH NO. 5 TAHUN 2014 KOTA SEMARANG TENTANG PENANGANAN ANAK JALANAN, GELANDANGAN, DAN PENGEMIS - Arif Kurnia Ardi Pradana; Margaretha Suryaningsih (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
This research aimed to clarify the role of the Stakeholders involved in implementing the policy on the handling of street children, hemeless, and beggars in the city of Semarang and explained the driving factor and a barrier to the implementation effort handling of street children, the homeless and beggars in the City of Semarang. Research methods uses qualitative exploration, the approach data collection with techniques observation, interviews, and study of the document. Informants in this study is the social service of the Semarang City, the NGO Yayasan Emas Indonesia, former street children, as well as the community. Data were analyzed with the theory of